The rise of income and the demise of class and social status? A systematic review of measures of socio-economic position in stratification research. (April 2022) - Barone, Carlo; Hertel, Florian R.; Smallenbroek, Oscar
Abstract: How empirical researchers measure socio-economic position is of great consequence for the understanding of different aspects of the stratification order and affects our conclusions about the causes and consequences of social inequalities. This article surveys social stratification research published in 2015–2019 in top-cited sociology journals to quantify the prevalence of the three approaches towards social position: income, class and social status. To study trends in researchers' measurement decisions over time, we compare with articles published in the same journals in 1995–1999. In both periods, income measures dominate stratification research and are gaining ground on class and social status measures over time. However the dominance of income differs between research areas. Intergenerational research on education and social mobility may be the last bastion of occupation-based measures. We also find that EGP-like schemes are largely prevalent within class analysis and have gained a paradigmatic status of a "one-size-fits-all" measure. We argue that these trends have profound implications for stratification research in sociology that may herald the death of class-analysis.